Multipolar and bulk modes: fundamentals of single-particle plasmonics through the advances in electron and photon techniques - Tsoulos Ted V.; Batson Philip E.; Fabris Laura (Nanophotonics, 2020)
Recent developments in the application of plasmonic nanoparticles have showcased the importance of understanding in detail their plasmonic resonances at the single-particle level. These resonances can be excited and probed through various methods, which can be grouped in four categories, depending on whether excitation and detection involve electrons (electron energy loss spectroscopy), photons (e.g., dark-field microscopy), or both (cathodoluminescence and photon-induced near-field electron microscopy). While both photon-based and electron-based methods have made great strides toward deepening our understanding of known plasmonic properties and discovering new ones, they have in general progressed in parallel, without much cross-pollination. This evolution can be primarily attributed to the different theoretical approaches driving these techniques, mainly dictated by the inherent different nature of electrons and photons. The discrepancies that still exist among them have hampered the development of a holistic approach to the characterization of plasmonic materials. In this review therefore, we aim to briefly present those electron-based and photon-based methods fundamental to the study of plasmonic properties at the single-particle level, with an eye to new behaviors involving multipolar, propagating, and bulk modes coexisting in colloidal nanostructures. By exploring the key fundamental discoveries in nanoparticle plasmonics achieved with these techniques, herein we assess how integrating this information could encourage the creation of a unified understanding of the various phenomena occurring in individual nanoparticles, which would benefit the plasmonics and electron microscopy communities alike.